2004
DOI: 10.1186/1471-2407-4-84
|View full text |Cite
|
Sign up to set email alerts
|

SMAC is expressed de novoin a subset of cervical cancer tumors

Abstract: Background: Smac/Diablo is a recently identified protein that is released from mitochondria after apoptotic stimuli. It binds IAPs, allowing caspase activation and cell death. In view of its activity it might participate in carcinogenesis. In the present study, we analyzed Smac expression in a panel of cervical cancer patients. Methods:We performed semi quantitative RT-PCR on 41 cervical tumor and 6 normal tissue samples. The study included 8 stage I cases; 16 stage II; 17 stage III; and a control group of 6 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
1
9
1
Order By: Relevance
“…In other studies conducted in RCC, no correlation between Smac/DIABLO and stage of disease was observed at the mRNA level (8,12). In cervical cancer, expression of Smac/DIABLO mRNA was not linked with tumor stage (17).…”
Section: Discussionmentioning
confidence: 74%
“…In other studies conducted in RCC, no correlation between Smac/DIABLO and stage of disease was observed at the mRNA level (8,12). In cervical cancer, expression of Smac/DIABLO mRNA was not linked with tumor stage (17).…”
Section: Discussionmentioning
confidence: 74%
“…The members of the inhibitor of apoptosis (IAP) protein family are highly expressed in several classes of cancer. Interestingly, recent studies revealed that Smac is also differentially expressed in cervical tumors and in tumor cell lines [19,20]. These observations have prompted researchers to design Smac mimetic compounds that can be administered either alone or in combination with other chemotherapeutic agents to kill tumor cells.…”
Section: Discussionmentioning
confidence: 98%
“…Smac/ Diablo mRNA is increased in cancer tissue compared with normal cervical tissue. 23 Hsp60 is elevated in breast cancer cells and correlates with metastatic potential and prognosis. 24 Overexpression of galactins is associated with increased tumor aggressiveness, metastasis and poor prognosis.…”
Section: Research Articlesmentioning
confidence: 99%